Aspects of Indo-European historical syntax in a typological perspective - Gvozdanović, Jadranka (Slovo a slovesnost, 2016)
This paper reexamines the core issues of the Indo-European syntax in a typological perspective including the interface of syntax, morphology and pragmatics (and in some instances also prosody). Word order is shown to have been significantly influenced by pragmatic functions even in allegedly prototypical verb-final systems in Anatolian, Indo-Aryan, Germanic and Romance. The paper also discusses the influence of verb valency involving clitic objects on attracting the verb to the initial position in Hellenistic Greek and Old Irish. Another major topic is the development of aspect systems that also had syntactic and pragmatic consequences. The paper discusses the main lines of this development including valency changes in a number of European language groups, whereas Indo-Aryan and Armenian (and to a limited extent also Germanic) primarily introduced other valency-changing categories, particularly causatives. The paper shows that the original typologicalproperties are relatively resistant to change, but areal contacts can play a mediating role as illustrated by Dravidian and Uralic.
Gesehen am 21.03.2025